Drying performance and overall energy requisite of industrial inclined bed paddy drying in Malaysia - Ibrahim, Mohd Nordin; Sarker, Md. Sazzat Hossain; Ab. Aziz, Norashikin; Punan, Mohd Salleh (School of Engineering, Taylor’s University College, 2014)
An attempt was undertaken to evaluate the performance of industrial inclined bed dryers (IBDs) in terms of drying capacity, drying rate, overall energy requisite and final quality of dried product in drying of freshly harvested paddy. In drying of paddy with initial moisture content of 22-23% wet basis (wb) to around 12.5% (wb) final moisture content, drying capacity and drying rate of the dryers were found to vary between 0.66 to 1.03 ton dry paddy/hour and 90 to 121 kg moisture/hour, respectively, for the holding capacity of each dryer at about 15 ton. The electrical energy consumption of the IBDs was found to vary between 18.15 to 27.55 kWh/t while the thermal energy consumption ranged between 960 to 1328.15 MJ/t. The IBDs operated at air temperature of 38-39°C yielded 1 to 4% higher head rice yield than the IBDs were operated at 41-42°C for drying of similar moist paddy, but milling recovery and whiteness were comparable.